2023
DOI: 10.1073/pnas.2305187120
|View full text |Cite
|
Sign up to set email alerts
|

DPPA5A suppresses the mutagenic TLS and MMEJ pathways by modulating the cryptic splicing of Rev1 and Polq in mouse embryonic stem cells

Abstract: Genetic alterations are often acquired during prolonged propagation of pluripotent stem cells (PSCs). This ruins the stem cell quality and hampers their full applications. Understanding how PSCs maintain genomic integrity would provide the clues to overcome the hurdle. It has been known that embryonic stem cells (ESCs) utilize high-fidelity pathways to ensure genomic stability, but the underlying mechanisms remain largely elusive. Here, we show that many DNA damage response and repair genes display differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…We found that genic collapsing analyses of individuals diagnosed with ALS identified known risk genes ( SOD1 , TARDBP , and TBK1 ) and a novel protective gene ( ALKBH3 ). ALKBH3 encodes for AlkB homolog 3, Alpha-Ketoglutarate Dependent Dioxygenase which protects against the cytotoxicity of methylating agents by repair of the specific DNA lesions [ 25 27 ]. ALKBH3 potentially acts as a putative hyperactive promotor to suppress transcription associated DNA damage of highly expressed genes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that genic collapsing analyses of individuals diagnosed with ALS identified known risk genes ( SOD1 , TARDBP , and TBK1 ) and a novel protective gene ( ALKBH3 ). ALKBH3 encodes for AlkB homolog 3, Alpha-Ketoglutarate Dependent Dioxygenase which protects against the cytotoxicity of methylating agents by repair of the specific DNA lesions [ 25 27 ]. ALKBH3 potentially acts as a putative hyperactive promotor to suppress transcription associated DNA damage of highly expressed genes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that genic burden testing of individuals diagnosed with ALS identified known risk genes (SOD1, TARDBP, and TBK1) and a novel protective gene (ALKBH3). ALKBH3 encodes for AlkB homolog 3, Alpha-Ketoglutarate Dependent Dioxygenase which protects against the cytotoxicity of methylating agents by repair of the specific DNA lesions (26)(27)(28). ALKBH3 potentially acts as a putative hyperactive promotor to suppress transcription associated DNA damage of highly expressed genes (29).…”
Section: Discussionmentioning
confidence: 99%
“…We found that genic burden testing of individuals diagnosed with ALS identified known risk genes ( SOD1 , TARDBP , and TBK1 ) and a novel protective gene ( ALKBH3 ). ALKBH3 encodes for AlkB homolog 3, Alpha-Ketoglutarate Dependent Dioxygenase which protects against the cytotoxicity of methylating agents by repair of the specific DNA lesions ( 26 28 ). ALKBH3 potentially acts as a putative hyperactive promotor to suppress transcription associated DNA damage of highly expressed genes ( 29 ).…”
Section: Discussionmentioning
confidence: 99%